Dispensador de cajetillas de cigarrillos para Mipyme como experiencia de relación academia-sector productivo, Tuluá - Lozada-Das-Dores, Ángel-José; Casallas-Restrepo, Ronald-Esteban; Bedoya-García, Jorge-Andrés; Castellanos-Garzón, Jenniffer-Alejandra; Rey-Piedrahita, Andrés (Revista Científica, 2021)
Through an academic research project, it was proposed to stablish a cooperation of three main actors in a society such as state, academia and productive sector (tertiary sector, retail), but keep in mind to incorporate people, in order to solve real-world problems of a MSMEs type called granero in Tuluá-Colombia. All this, based on triple and quadruple helix model’s application, that seek scientific and technological development of a society to achieve a general and sustainable quality of life over time. Through unstructured observation, document review and open interviews with MSME manager and employees, the data related to company characteristics were collected. Based on this information, it proceeded to establish the current situation and study the solution that best match needs and requirements of the company. Then, the cigarette pack dispenser machine was designed and developed. Measurement of dispatch and customer service times and the lost products inventory, allowed to verify the machine efficiency. Design and development of the dispensing machine allow to evidenced that academy-company-state-people interrelation and cooperation is feasible and useful to solve real life problems in organizations. In addition, a greater participation of civil society and increase the academy-company-state cooperation and society cooperation over time was evidenced.